On H-Irregularity Strength of Grid Graphs - Meilin Imelda Tilukay (Department of Mathematics, Faculty of Mathematics and Natural Sciences, Pattimura University, Ambon, Indonesia, 2020)
This paper deals with three graph characteristics related to graph covering named the (vertex, edge, and total, resp.) –irregularity strength of a graph admitting -covering. Those are the minimum values of positive integer such that has an -irregular (vertex, edge, and total, resp.) -labeling. The exact values of this three graph characteristics are determined for grid graph admitting grid-covering,